ANALISIS EFEKTIVITAS PELATIHAN INTERHOTEL TRANSFER PADA KARYAWAN ASTON TANJUNGPINANG HOTEL & CONFERENCE CENTER - Octojaya Abriyoso; Putri Dewi Safitri; Nanda Kristia Santoso; Alfi Hendri (Bajang Institute, 2024)
The purpose of this study was to determine the effectiveness of Interhotel Transfer training on Aston Tanjungpinang Hotel & Conference Center employees. This study used a sample of 5 informants using a non-probability sample technique, namely purposive sampling. The method used in this research is a qualitative method. With the object of research Aston Tanjungpinang Hotel & Conference Center. Data collection is done in two ways, namely interviews and documentation. Where the informant answers as many as 9 statement items related to the variables measured. The results of the interview will be processed using data reduction techniques, data presentation and data conclusion. After that, it will be analyzed by testing the validity of the data using the source triangulation technique. The results of research on the effectiveness of Interhotel Transfer Training on Aston Tanjungpinang Hotel & Conference Center employees are said to be quite effective, because the training can provide changes in thinking patterns, better work motivation to develop their careers